Sistem Pendukung Keputusan Pengoptimalan Pembagian Tugas dengan Kombinasi Metode Hungarian dan Permutasi - Julianto Lemantara (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
In order to solve the assignment problems, so far commercial applications only offer one optimal solution and cannot handle the assessment process that has some criteria, such as Microsoft Excel and WinQSB. Limitations of commercial applications have been already solved in previous research, however, it still have two deficiencies, i.e. a number of tasks and workers have to be same and cannot include subcriteria. When the application is able to handle the deficiencies, it will be aimed to solve the real case more properly. The proposed methods to solve the assessment problem are Hungarian and Permutation method. This paper implements a method, called System Development Life Cycle (SDLC) in the waterfall model. Through new assignment application, the optimal solution that is offered to the decision maker may have more than one solution, which the number of tasks can be different with the number of workers. Furthermore, the assignment application is able to produce solution for the assignment problem comprehensively because the task assessment has included criteria and subcriteria.